2021
DOI: 10.1186/s12889-021-10489-2
|View full text |Cite
|
Sign up to set email alerts
|

Geographic reach and nutritional quality of foods available from mobile online food delivery service applications: novel opportunities for retail food environment surveillance

Abstract: Background Online Food Delivery Services (OFDS) have rapidly expanded in North America, but their implications for geographic access to food and potential dietary outcomes of their use are poorly understood. The purpose of this paper is to examine the extent to which OFDS may geographically expand retail food environments. A secondary objective is to evaluate the healthfulness of foods available on mobile OFDS in a large Canadian city using the Healthy Eating Index-2015 (HEI-2015). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 18 publications
2
38
0
Order By: Relevance
“…A Canadian study analyzed the full menus of retailers partnering with a large OFDS and similarly found low Healthy Eating Index-2015 scores—ranging from 19.95 to 50.78 out of 100 (with a score of 100 being the healthiest) ( 13 ). This study also found a mean delivery distance of 3.7 km or 2.3 miles measuring from postal codes in Ontario to online food retailers ( 13 ).…”
Section: Junk Food On Demand: Impact On Nutrition Health and Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…A Canadian study analyzed the full menus of retailers partnering with a large OFDS and similarly found low Healthy Eating Index-2015 scores—ranging from 19.95 to 50.78 out of 100 (with a score of 100 being the healthiest) ( 13 ). This study also found a mean delivery distance of 3.7 km or 2.3 miles measuring from postal codes in Ontario to online food retailers ( 13 ).…”
Section: Junk Food On Demand: Impact On Nutrition Health and Wellbeingmentioning
confidence: 99%
“…A Canadian study analyzed the full menus of retailers partnering with a large OFDS and similarly found low Healthy Eating Index-2015 scores—ranging from 19.95 to 50.78 out of 100 (with a score of 100 being the healthiest) ( 13 ). This study also found a mean delivery distance of 3.7 km or 2.3 miles measuring from postal codes in Ontario to online food retailers ( 13 ). Australian research has likewise, demonstrated that the mean delivery distance from food outlet to suburbs was 3 km, and around 90% of delivery distances were greater than 1 km ( 7 )—a distance that typically defines the neighborhood food environment.…”
Section: Junk Food On Demand: Impact On Nutrition Health and Wellbeingmentioning
confidence: 99%
“…Internationally, other studies have found similar results, suggesting that the OFD platform environment does not promote healthiness. In Canada, the quality of food on offer in the menus of 12 restaurants on four popular OFD platforms was considered poor (HEI-2015 score ranged from 19.95 to 50.78 out of 100) (9) . In Australia and New Zealand, the most popular food outlets registered on one OFD platform have been classified as 'unhealthy', with 85.9% of all popular menu items being discretionary (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies from many parts of the world have highlighted the wide range of unhealthy food items on offer on these platforms and their frequent use of strategies that promote unhealthy eating practices (8)(9)(10)(11) . For example, many platforms use a combination of marketing strategies such as special offers, recommendations and 'combo' deals to maximise consumers' purchases.…”
mentioning
confidence: 99%
“…The national trend for increased availability of online food ordering [17,18] was reflected in this rural Appalachian community. Although food delivery applications may offer expansion of retail food environments to individuals living further distances, dietary quality scores of these food delivery restaurants have fallen short [48], leaving delivery as a counterintuitive new resource to supply nutritionally adequate foods (i.e., balanced, diverse, dietary pattern meeting sufficient personal energy and nutrient requirements to maintain good health) to those with limited access. Likewise, utilization of these resources can be determined by income level, access to smartphone or internet services, and delivery distance [49].…”
Section: Discussionmentioning
confidence: 99%